Self-medication in hospitalized patients with COVID-19: A cross-sectional study in northern Peru - Vasquez-Elera, Luis E. (2022)
Introduction This study aimed to identify factors associated with self-medication in patients with COVID-19. Methods A cross-sectional study was conducted using medical records of patients with COVID-19 who self-medicated before admission to a hospital in Piura, Peru. Prevalence ratios and 95% confidence intervals were estimated using generalized linear models with Poisson distribution family, log link function, and robust variance. Results Out of 301 patients, 165 (54.8%) self-medicated before hospital admission, being more frequent self-medication with ivermectin (85.5%) and azithromycin (71.5%). The frequency of self-medication in those aged between 30-59 years was 2.53-fold higher than in those between 18-29 years. Male patients, dyslipidemia, smoking, and hepatic steatosis were associated with self-medication. Clinical characteristics associated with self-medication were fever, cough, headache, anosmia, dysgeusia, nausea/vomiting, and gastroesophageal reflux. Conclusions A high frequency of self-medication before hospital admission was observed in Peruvian patients with COVID-19, mainly of drugs without proven efficacy.